Efficacy and Safety of Gabapentine and Duloxetine in Diabetic Peripheral Neuropathic Pain - Ahmad, Hussain; Rahman, KM Hafizur; Chowdhury, Miftaul Jannat; Bhuiya, Monharul Islam; Ferdous, Nurjahan; Chowdhury, Md Abu Nayeem (Medicine Today, 2021)
Introduction: Diabetic peripheral neuropathy (DPNP) is not uncommon now a days. As the pathophysiology is not completely understood, symptoms relief is still the main goal of treatment. Gabapentine and Duloxetine are being using around the world for this purpose. But clinical data regarding its efficacy and safety are not sufficiently available. Materials and Methods: This prospective comparative clinical study conducted in Sylhet MAG Osmani Medical College and Sylhet Diabetic Hospital, Bangladesh from January 2013 to December 2013. Diagnosis of DPNP confirmed by Michigan Neuropathy Screening Instrument (MNSI) and Douleur Neuropathic en-4 (DN4). Patients were treated by Gabapentine (Group-A) and Duloxetine (Group-B); and followed up at 4th, 8th and 12th week of treatment using 11-point numerical pain rating scale (NRS), clinical global impression of change (CGIC) score and patient’s global impression of change (PGIC) score. Results: A total of 72 patients with DPNP were recruited. Final comparison was done in 64 patients – 33 in Group-A and 31 in Group-B. Changes in NRS (p = <0.001), CGIC (p = <0.001) and PGIC (p = <0.001) were statistically significant during the course of treatment. However, inter-group variation of NRS, CGIC and PGIC were not statistically significant at the beginning and 4th, 8th and 12th week of treatment. Insignificant adverse effects were noted between the groups in this study except constipation (p = 0.022) and nausea-vomiting (p = 0.01) of Duloxetine taking group. Conclusion: Gabapentine and Duloxetine are equally effective in the treatment of DPNP with good safety profile. Medicine Today 2021 Vol.33(2): 108-113